Anatomy of the New Testament : a guide to its structure and meaning - Spivey, Robert A., 1931-; Black, C. Clifton (Carl Clifton), 1955-; Smith, D. Moody (Dwight Moody) (Fortress Press, 2019)
"Now in its 8th edition, Anatomy of the New Testament is one of the most trust-worthy and enduring introductory textbooks of its kind. Its authors bring literary and historical approaches to the New Testament together, offering a comprehensive and accessible approach that appeals to students at all levels. Visually appealing and well-designed this compact edition has been designed for today's student, and is illustrated with engaging images, refreshed maps, and updated bibliographies that make the textbook enjoyable to read and easy to teach. The stand-out pedagogical features have been updated as well, updated for new advances in biblical scholarship and the needs of today's student: Have You Learned it? Offering questions for analysis and reflection; What Do They Mean? Presenting definitions for key terms to enhance student comprehension and critical thinking."